Dampak rendahnya literasi terhadap permasalahan sosial - Az Zahra, Ghefira (Maliki Interdisciplinary Journal, 2023)
Literacy is a person’s ability to use their potential and skills in processing and understanding information when carrying out reading or writing activities. The intensity level of one’s literacy will affect the level of quality of life of everyone. The higher the literacy culture that exists, the better the quality of education in the area will improve and cause widespread prosperity. A low literacy culture can cause a variety of significant impacts. These impacts eventually become various kinds of social problems that occur in society. Social problems are conflicts between elements of culture or society, which endanger the life of a social group, or hinder the achievement of the basic desires of members of the social group, causing social bond instability.